Understanding rumour conceptions, forms, dissemination and control at workplace : narratives from the employees / Mohd Mursyiddin Abdul Manaf - Abdul Manaf, Mohd Mursyiddin (Institute of Graduate Studies, UiTM, 2013)
This qualitative research focuses on the problem of understanding how private and public sector employees make sense and unconsciously be involved in rumour phenomenon in their organisations. This problem is addressed through four objectives - 1) to identify the main factors that trigger the conception of rumours in workplace, 2) to explore the most possible types/forms of rumours that circulate among the employees in their workplace, 3) to understand the raison d’être of rumours being disseminated by employees in their workplace, and 4) to determine the best measures taken by the employees in managing rumour spread at their workplace. Data for this entire research is gathered through in-depth interviews, which involved 15 informants that had been chosen through purposive sampling, aided by criterion-based selection and being conducted through theoretical sampling. These findings were categorised into four sections. Firstly, in terms of rumours conception, data from informants have contributed to 15 themes that can be considered as pertain to content and pertain to functions. Secondly, the researcher posed few basic questions on the forms and fallout of rumours to the informants…